历史思想的文学叙述:《儒林外史》人物形象析论 - 刘, 文杰 (2023)
《儒林外史》是吴敬梓创作的章回体长篇小说，其作为一幅清朝十八世纪时描写士林的风俗画，生动形象地描绘出了当时士人的历史命运与生存处境，被喻为中国古典小说史上“思想家的小说”。作者运用反讽的艺术手法，集毕生精华于一书，塑造了全书三百多个生动的人物形象。自成书以来，由于它独特的视角与艺术结构，吸引了世界众多学者的研究，他们分别从小说叙述、作品结构、科举制度、作者自身等方面展开了多姿多彩的学术探讨。研究他的文学作品自然离不开对作家思想的探讨，然而吴氏的思想是复杂且丰富的，这种复杂性在作者的生活以及文学创作中都有较为明显的体现。由于小说人物背后大都实有其人这一特殊性，因此可以很好地使用哲学家柯林伍德的历史思想法，结合作者自身经历对其展开研究。这对进一步研究《儒林外史》的思想内涵，具有重要的学术价值.本文结合吴氏自身经历，重现吴敬梓过去的事实于我的脑海中。沿着历史思想——历史就是思想史——重演历史思想作为研究主线，结合小说深入探究人物创作背后之目的，对人物形象进行脉络梳理，揭示书中人物形象的个性与共性，了解作者寄寓在人物身上的深层含义，以更好地挖掘小说文本的思想内涵与文化意蕴。从作者的历史思想角度探究小说人物形象塑造，可以让我们更加了解作者对当时世风的批判以及向往的生活，充分了解作者愤世及救世意识。他对社会弊病展开反思，推崇颜李实学的他对虚空不实的程朱理学展开批判，务实践，求真实的精神阐发，以期达到重建礼乐秩序的目的；出身官宦世家的他，受家庭影响，从汲汲于求取官位到对官本位思想展开反思，用批判的眼光重新审慎过去沉溺其中的人生欲求，对功名富贵深恶痛绝，警醒仕人们要有社会责任感；他的社会责任感使得他不得不在入世与出世间难以抉择，最终选择了贡献自己力量德化世人，这正是吴氏敏锐的反思观和社会责任感的鲜明体现；最终吴敬梓用建功立业、轻功名富贵、淳朴有个性者寄托了自己所向往的理想社会，但是这些人物也许还诉说着作者面对社会现实，不得不选择的失败、超脱与逃避，这些理想都因缺乏现实基础而显得无力的不切实际。可见，以柯林伍德的西方历史学角度审视之，它为中国反讽小说提供了新思路。The Scholars is a long fiction written by Wu Jingzi in the form of a chapter book. It is a painting depicting the customs of scholars in the 18th century of Qing Dynasty, it vividly depicts the historical fate and survival of the scholars at that time, andhas been described as a "fiction of thinkers" in the history of classical Chinese fiction. Using the artistic technique of irony, the author has gathered the essence of his lifeinto one book, creating more than 300 vivid characters throughout the book. Since its inception, due to its unique perspective and artistic structure. The Scholars has attracted many scholars around the world, who have launched various academicdiscussions on the fiction's narrative, the structure of the work, the imperial examination system, and the author himself. The study of his literary works is naturally inseparable from the exploration of the writer's thoughts, but Wu's thoughts are complex and rich, and this complexity is evident in the author's life as well as inhis literary creations. Because of the particularity that most of the fictional characters are real people, it is possible to make good use of the philosopher Collingwood's method of historical thought and to study them in the context of the author's ownexperience. This is an important academic value for further research ontheideological connotations of The Scholars. This paper combines Wu's own experiences to recreate the facts of Wu Jingzi's past in my mind. This paper follows the historical thought - history is the history of thought - reenactment of historical thought as themain line of research, explores in depth the purpose behind the creation of thecharacters in conjunction with the fiction, composes the veins of the characters, reveals the individuality and commonality of the characters in the book, understands the deeper meaning that the author pinned on the characters, in order to better explorethe ideological connotation and cultural implications of the fiction text. Exploringthefiction's characterization from the perspective of the author's historical thought cangive us a better understanding of the author's criticism of the world style of the timeand the life he aspired to, and a full understanding of the author's sense of indignationand salvation. The author reflects on the social ills, and the author, who respectedYanand Li's practical science, criticizes the vain and insubstantial Cheng and Zhuphilosophy, and seeks to put into practice the real spiritual exposition in order toachieve the purpose of rebuilding the order of ritual and music; coming froma familyof officials, he is influenced by his family, from seeking official positions to reflectingon the idea of the official position, re-examining with a critical eye the past indulgence in life's desires, abhorring fame and wealth, and reminding people of social responsibility. His sense of social responsibility makes it difficult for himtochoose between entering the world and leaving the world, and he finally chooses tocontribute his own strength to virtue the world, which is the distinctive embodiment of Wu's keen reflective outlook and sense of social responsibility; ultimately, WuJingzi uses those who build a successful career, who are light on fame and wealth, andwho are simple and have individuality to put forward the ideal society to whichheaspires, but these characters may also speak of the failure, transcendence and escapethat the author had to choose in the face of social reality, and these ideals areimpotently impractical due to the lack of realistic foundation. As can be seen, it offersnew ideas for Chinese ironic fiction when examined through the lens of R.G. Collingwood's Western historiography.